Oxytocin receptor gene methylation and substance use problems among young African American men. (1st November 2018) - Kogan, Steven M.; Cho, Junhan; Beach, Steven R.H.; Smith, Alicia K.; Nishitani, Shota
Highlights: Oxytocin receptor gene ( OXTR ) methylation predicts substance use problems among young African American men. OXTR methylation predicts fewer supportive prosocial ties among African American men. Prosocial ties may deter substance use problems via reductions in OXTR methylation. Abstract: Background: Stressful or supportive social environments promote biological changes with regulatory implications for future relationships and substance abuse. Recent research suggests links between adverse social environments, prosocial relationships, methylation at the oxytocin receptor gene ( OXTR ), and substance abuse. The potential for OXTR methylation to act as the mechanism linking social environments to substance abuse has yet to be investigated. We hypothesized that, for young African American men, childhood adversity increases, and supportive, prosocial bonds with parents, peers, partners, and community mentors decrease OXTR methylation levels, which in turn predict increases in substance-related symptoms. Methods: A sample of 358 rural African American men (age 19 at baseline) provided self-report data at three time points separated by 18 months and a genetic specimen at Time 2. Results: Early adversity was associated with OXTR methylation indirectly via contemporary prosocial relationships. OXTR methylation was a proximal predictor of changes in substance-related symptoms. We found no evidence for a direct association of self-reported childhood trauma with OXTR methylation status. Conclusions: Findings suggest that OXTR methylation is linked to substance use symptomatology, ostensibly resulting in increased expression of oxytocin (OT) in peripheral and central nervous systems. OXTR may act as a mechanism to explain how prosocial ties deter substance abuse and related problems. Despite conjectures in the literature that early adversity may become physiologically embedded via methylation in the OT system, direct effects were not evident. Rather, early adversity may affect OXTR methylation via influence on contemporary prosocial relationships.